Ring of confidence : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Palmerston North, New Zealand - Aoina, Ailaoa Maureen (Massey University, 2006)
This is an exploratory study of how eight Year 12 and Year 13 Pacific teenage females living in Auckland and Rotorua defined the concept of confidence and examines how they perceived family, church, school, friends and community influencing their confidence levels, either positively or negatively, and what factors they believed could help to improve their confidence levels in these different settings. A comparison of the two sample groups from Rotorua and Auckland was undertaken to determine whether living in a community where Pacific people are either the majority or minority, impacts differently on their overall confidence. It is within this framework that this study will discuss how the Pacific teenage female's confidence contributed to their own psychological wellbeing. The semi-structured interviews and focus groups were the techniques used to collect rich qualitative data. The general inductive approach was used to analyse the qualitative data related to the research objectives. Specific categories and themes were developed which captured core messages reported by the participants. Categories that emerged for positive influences on confidence included 'encouragement, enjoyment, development, achievement, and spirituality / cultural identity'. For negative influences, categories included 'judgment, the fear of, family / friends, and culture'. Ways to improve one's confidence highlighted categories of 'communication, motivation, and enjoyment'. Living in a community where Pacific people are either the minority or the majority does have some impact on the confidence development of participants. All the participants agreed that having confidence enabled them to make decisions about study, career goals, as well as broader life choices, and that all these factors contributed to their psychological well-being. This study suggests ways confidence can be improved and the results are discussed in terms of the theories of perceived competence, self efficacy, motivation goal theory, and the social exchange model, and how motivational issues relate to one's psychological wellbeing.
Keywords: New Zealand; Confidence; Self-confidence; Teenage girls -- Psychology; Pacific Islanders -- Psychology